ChemInform Abstract: Dye‐Sensitized Semiconductors Modified with Molecular Catalysts for Light‐Driven H2 Production. Issue 7 (January 2016) - Willkomm, Janina; Orchard, Katherine L.; Reynal, Anna; Pastor, Ernest; Durrant, James R.; Reisner, Erwin
Abstract: Review: 50 refs.